BATAKO SEKAM PADI KOMPOSIT MORTAR SEMEN - Sumaryanto, Dedy; Satyarno, Iman; Tjokrodimulyo, Kardiyono (Civil Engineering Forum Teknik Sipil, 2009)
Several previous construction material researches on exploiting rice husk as wall panel (concrete block), showed that rice husk mixed with construction material gave lighter weight but lower strength. This research attempted to improve the strength of the concrete block composite by giving cement mortar mixture as the outer layer. The specimen of concrete block composite was made under the concrete principal method. The first step was to put the concrete block composite and rice husk into a mold in various thickness of required outer layer. Then cement mortar mixture was poured around it as the outer layer. The results showed that the compressive strength of concrete block for various outer layer thickness without cord net ranging from 5 mm, 10 mm, and 15 mm were reached at 1,68 MPa, 5,16 MPa and 6,51 MPa, respectively and per mÂ² wall weight of 102,44 kgs, 122,46 kgs, and 139,10 kgs, respectively. The compressive strength of concrete block with cord net for the same outer layer thickness variation were reached at 1,97 MPa, 5,72 MPa and 6,70 MPa, respectively and per mÂ² wall weight of 120,40 kgs, 135,98 kgs, and 152,23 kgs. Water absorption of outer layer achieved were 2,01% and 7,06% after 10 minutes and 24 hours soaking, respectively. The optimum outer layer thickness without cord net of concrete block composite with rice husk was 10 mm, which met the requirements of minimum compressive strength, light weighted and economic cost aspects.